APPLICATION OF DISCUSSION METHOD IN IMPROVING STUDENT LEARNING OUTCOMES IN PAI SUBJECTS - Faisal Faliyandra; Abdelmajid Idris Mohammed Khalil; Makhrus Ali, M. (International Journal of Multidisciplinary Reseach, 2025)
Achievement​ results Study past order method discussion Can tried with evaluation. Evaluation is a series activity use take into account something activity so that recognize throughout the activity the Already bear fruit results. The formulation of the problem in this study is